Orchid modern : living & designing with the world's most elegant houseplants - Hachadourian, Marc (Timber Press, Inc., in association with The New York Botanical Garden, 2019)
Add the vibrant colors and exotic blooms of orchids to your houseplant haven--it's easier than you think with the help of Orchid Modern. Marc Hachadourian, the curator of the orchid collection at the New York Botanical Garden, shares his secrets to successfully growing these sometimes finicky houseplants. Besides the basics, you'll learn his top 120 orchid picks for green and not-so-green thumbs. Ten inspirational, step-by-step projects, including terrariums, a wreath, and a kokedama, provide the confidence to make orchids a thriving, vivid part of your home's signature style.